Un beso de Dick, al diablo la maldita primavera, como esta tarde para siempre: propuesta literaria para el currículo escolar y ruptura con la heteronormatividad del canon literario en la educación colombiana (2019)
Un beso de Dick, Al diablo la maldita primavera, Como esta tarde para siempre: literary proposal for the school curriculum and rupture with the heteronormativity of the literary canon in Colombian education, is a research work that moves through the branches of education, literature and social reality to focus on the rupture of heteronormative parameters of power to allow the growth of the literary field in school, in order to generate encounters with sexual diversity. Thus, it focuses on proposing the growth of literature in the eighth and ninth grades, from the immersion of different works belonging to the category of queer or homosexual literature to the Colombian literary canon. For the above, through a hermeneutical methodology, eleven reading plans of educational institutions and schools of Valle de Aburra are collected, to which a comparative analysis is carried out, generating as a result that only one of the eleven reading plans uses a novel that convenes the homosexual theme. Hence, three works that analyze and are understood from the point of view of theorists like Judith Butler and Michael Foucault are postulated as they contribute to the needs of the school reality, in which dynamics of inclusion, respect and understanding of social ideological changes are not manifested, and that education is able to achieve.